2015
DOI: 10.1186/s13046-015-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy by 3-MA enhances IL-24-induced apoptosis in human oral squamous cell carcinoma cells

Abstract: BackgroundInterleukin-24(IL-24), also referred to as melanoma differentiation-associated gene-7(mda-7), is a unique member of the IL-10 gene family, which displays nearly ubiquitous cancer-specific toxicity. The most notable feature of IL-24 is selectively induced growth suppression and apoptosis in various cancer cells, with no harmful effects toward normal cells. Autophagy is a self-protective mechanism in many kinds of tumor cells that respond to anticancer treatment. It is reported that autophagy inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
(22 reference statements)
4
29
0
Order By: Relevance
“…4A). Using the autophagy inhibitor 3-methyladenine (20), similar, but less pronounced proliferation effects were seen in both B16 and ID8agg cells (data not shown).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…4A). Using the autophagy inhibitor 3-methyladenine (20), similar, but less pronounced proliferation effects were seen in both B16 and ID8agg cells (data not shown).…”
Section: Resultsmentioning
confidence: 83%
“…For pharmacologic autophagy inhibition in vivo , mice were injected intraperitoneally with chloroquine 60 mg/kg every other day (18,19) or 3-methyladenine 25 mg/kg every 5 days (20) versus PBS control starting on day 7 following tumor challenge, regimens shown to inhibit tumor cell autophagy effectively in vivo .…”
Section: Methodsmentioning
confidence: 99%
“…In order to further confirm the role of IL-17/IL-17R and the JAK2/STAT3 signaling pathway in the induction of autophagy and inhibition of apoptosis, SMMC-7721 cells were treated with 3-methyladenine (3-MA; 10 mM; Sigma-Aldrich; Merck Millipore), which is a known inhibitor of autophagy (41), and AG490 to inhibit the JAK2/STAT3 signaling pathway. Compared with the cells treated with oxaliplatin only, the AG490-and oxaliplatin-treated cells expressed less BCL-2 and more BAX, which indicated that apoptosis was induced to a greater extent in these cells.…”
Section: Il-17/il-17r Induces Autophagy In Smmc-7721 Cells Throughmentioning
confidence: 99%
“…IL-24 expression is lost in most cancer cells of human origin [2][3][4]. Studies have shown that loss of IL-24 expression is correlated with disease progression in prostate cancer [5], breast cancer [6], colon cancer [7], neuroblastoma [8], acute leukemia [9], oral squamous cell carcinoma [10,11], lung cancer [12] and other cancers [13][14][15][16][17]. Exogenous IL-24 expression has anti-tumor, anti-angiogenic and anti-metastatic properties and suppresses various signaling pathways, without harming normal cells [2][3][4][5].…”
mentioning
confidence: 99%